Project management at information professionals’ education: international analysis in the Library and Information Science curriculum - Cobo Serrano, Silvia (Revista General de Información y Documentación, 2016)
The paper aims at analyzing the university training on project management that can be offered to information students and professionals. In order to achieve this goal, international Library and Information Science curricula have been analyzed. In this line, different works and directories on Library and Information Science education have been used for this purpose. As a result, the database created lets us know the 106 courses on project management included in the curriculum around the world. Finally, the analysis is focused on the following indicators: geographical items, universities, graduates and postgraduate programs and, lastly, courses on project management in the Library and Information Science context.
Keywords: Curriculum analysis; library and information science; teaching; university training; project management